2016
DOI: 10.48550/arxiv.1604.07959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First-principles simulations of glass-formers

Abstract: In this article we review results of computer simulation of glasses carried out using first principles approaches, notably density functional theory. We start with a brief introduction to this method and compare the pros and cons of this approach with the ones of simulations with classical potentials. This is followed by a discussion of simulation results of various glass-forming systems that have been obtained via ab initio simulations and that demonstrate the usefulness of this approach to understand the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 99 publications
2
4
0
Order By: Relevance
“…The results show a slight postshift at 120 cm −1 and a preshift at 1100 cm −1 for doped NBS compared to NBS, which might be associated with the weakening of the Si−O BO −Si network and increasing Si−O NBO with doping of the glass matrix. The reported peak positions can be found in good agreement with the studies reported by Kob and Ispas55 for the NBS glass matrix. Since the glassy state of a similar NBO shares very similar peak positions, only negligible differences were noticed for doped glasses compared to the NBS glass matrix, however, a significant change can be noticed for NBS or doped NBS matrix compared to the pure glass matrix of SiO 2 and B 2 O 3 .…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The results show a slight postshift at 120 cm −1 and a preshift at 1100 cm −1 for doped NBS compared to NBS, which might be associated with the weakening of the Si−O BO −Si network and increasing Si−O NBO with doping of the glass matrix. The reported peak positions can be found in good agreement with the studies reported by Kob and Ispas55 for the NBS glass matrix. Since the glassy state of a similar NBO shares very similar peak positions, only negligible differences were noticed for doped glasses compared to the NBS glass matrix, however, a significant change can be noticed for NBS or doped NBS matrix compared to the pure glass matrix of SiO 2 and B 2 O 3 .…”
supporting
confidence: 90%
“…The peak broadening is seen to have significantly reduced in the case of first principles studies as well as in the experimental studies of VDOS for SiO 2 . 55,56 Nevertheless, such a flat structure of VDOS of SiO 2 at the lower frequency zone is not new but has been reported by many earlier MD simulation studies. 55,56 Further, the peaks at higher frequency ∼1050−1070 cm −1 in the VDOS of SiO 2 capture well the modes concerning intra-tetrahedral excitations.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Computer simulations have by now been established to be a highly valuable tool to get insight into the properties of complex systems such as liquids and glasses [1,2,3]. The most important ingredient for such simulations is the interaction potential between the particles since its accuracy is crucial for obtaining a reliable description of the properties of the material on the micro-and macroscopic scale.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is far from obvious whether or not such classical MD simulations are able to give a quantitative correct description of the local structure of the surface since the arrangement of the atoms is very different from the one encountered in the bulk. This problem can be avoided by using an ab initio approach in which the forces are directly calculated from the electronic degrees of freedom [45]. This approach is thus not only more reliable but in addition it also allows to determine the electronic signatures of the main structural features of samples with surfaces.…”
Section: Introductionmentioning
confidence: 99%